Granger causal nexus between good public governance and unemployment: Evidence from cross-country panel data investigation - Cristina Boţa-Avram; Adrian Groșanu; Paula-Ramona Răchișan; Sorin Romulus Berinde (Journal of Risk and Financial Management, 2021)
The purpose of this paper is to investigate the causality between good public governance captured through six World Bank governance indicators and unemployment rate (unemployment as % of the total labour force) as a clear indicator of labour market performance. Although some previous papers have empirically demonstrated the casual nexus between country-level governance and economic development, this study investigates the relation of causality between public governance and the labour market. By employing Granger non-causality tests, we tested two hypotheses with regard to this nexus. We argue that bidirectional Granger causality is predominant for the relation of country-level governance and unemployment. Finally, our paper offers a complex quantitative analysis of the causal nexus between public governance quality and one of the most known labour market activity indicators for an extended panel dataset of countries worldwide for 10 years.
Keywords: 330; country-level governance; Granger non-causality test; sustainable economic development; unemployment as % of the total labour force; vector error correction model